The obligations of parties in the maintenance of leased properties (2011)
The lease of real estate is one of the contractual arrangements with a greatest social impact in the Colombiancontext. Indeed, the national real estate trade associations(Fedelonjas and Camacol), related to the property business,consider that in the country there are about 20.000.000leased buildings, they intended to serve as family housing,such as physical unit for the operation of a establishmentof trade, as an ofﬁce for the exercise of a profession andin order for other activities related to the daily lives of theColombian people.This article aims to conduct a review of the regulationsconcerning the obligations acquire the parties (lessor andlessee) in the lease, at the point of maintenance, repairand/or improvements occurring in the leased property,unveiling the gaps and legal inconsistencies were foundin the standard and formulating positions or viewpointsto solve such outrages of the legislature